Apple Peel Small Bowel, A Review of Four Cases: Surgical and Radiographic Aspects - Akinola, RA; Osuoji, RL (Journal of Nepal Paediatric Society, 2011)
Background: Although apple peel intestinal atresia is rare and is associated with a high mortality and morbidity, there is a dearth of its report in African literature. This study reviews four of the cases seen in a state teaching hospital in Lagos, considering the radiographic findings, surgical management and outcome. A brief review of literature is also undertaken. Aims and Objectives: To correle the plain radiographic findings with the surgical findings of neonates gathered over a six year period and to evaluate their surgical management, hoping to further help improve management of such neonates’ in future in resource limited regions such as ours. Methodology: It was a retrospective case series of four neonates who were brought in over a period of six years and operated after an initial plain abdominal X-ray. They were done as emergency cases, consent was obtained from their parents and the study was approved by the research and ethics committee. Operative findings were subsequently correlated with their radiographic findings and the surgical outcomes and follow up were documented. Conclusion: This study revealed that “the triple bubble sign” is a common radiographic finding in Apple Peel deformities, as well as gangrene of the jejunum and ileum at surgery. Key words: Apple peel atresia; Jejunoileal atresia; Plain Abdominal Radiography; Parenteral nutrition; Short Bowel Syndrome. DOI: http://dx.doi.org/10.3126/jnps.v31i3.5037 J Nep Paedtr Soc 2011;31(3): 227-234